Thermodynamics, environmental damage cost, exergoeconomic, life cycle, and exergoenvironmental analyses of a JP-8 fueled turbodiesel aviation engine at take-off phase. (March 2023) - Korba, Peter; Balli, Ozgur; Caliskan, Hakan; Al-Rabeei, Samer; Kale, Utku
Abstract: The objective of this study is to evaluate the energetic, exergetic, sustainability, economic and environmental performances of a 4-cylinder turbodiesel aviation engine (TdAE) used on unmanned aerial vehicles for the take-off operation mode to assess the system with large aspects. Energy efficiency of the system is found as 43.158%, while exergy efficiency 40.655%. Thermoeconomic analysis gives information about the costs of the inlet and outlet energy and exergy flows of the engine. Hourly levelized total cost flow of the TdAE is found as 21.036 /h, when the hourly fuel cost flow of the engine is found as 30.328 /h. The waste exergy cost parameter is determined as 0.0144 MJ/h/ from exergy cost-energy-mass (EXCEM) analysis, while it is estimated as 14.043 MJ/ from modified-EXCEM analysis. Environmental damage cost analysis evaluates the cost formation of the exhaust emissions. The total environmental damage cost of the TdAE is computed as 12.895 /h whilst specific environmental damage cost is determined as 0.054 /MJ for 494.145 MJ/h TdAE power production. It is assessed that the main contributors to the environmental impact rate of the TdAE are the fuel consumption and the formation pollutants of combustion reaction.